(untitled) (International Journal of Medical and Surgical Sciences, 2019)
The number of people infected with the Human Immunodeficiency Virus (HIV) in Chile, and especially in the Biobío region, has increased over the last decade, which constitutes a warning sign for healthcare in our country. HIV infection is strongly conditioned by social factors, such as stigma and discrimination, which still are associated with it. These stigmas are manifested in various forms and lead to complex consequences that have a negative influence on prevention, diagnosis, treatment and quality of life. Therefore, it is necessary to identify them, in order to propose education strategies for managing HIV patients, starting from the academic training of healthcare students, who as future professionals will probably be in touch with these patients. The objective of this article is to review the phenomenon of social stigma in health care to people with HIV/AIDS by healthcare professionals and students.